2004
DOI: 10.1093/cercor/bhh186
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Subcomponents within the Superior Longitudinal Fascicle in Humans: A Quantitative, In Vivo, DT-MRI Study

Abstract: Previous research in non-human primates has shown that the superior longitudinal fascicle (SLF), a major intrahemispheric fiber tract, is actually composed of four separate components. In humans, only post-mortem investigations have been available to examine the trajectory of this tract. This study evaluates the hypothesis that the four subcomponents observed in non-human primates can also be found in the human brain using in vivo diffusion tensor magnetic resonance imaging (DT-MRI). The results of our study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

57
869
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,066 publications
(934 citation statements)
references
References 70 publications
57
869
2
6
Order By: Relevance
“…White matter alteration in ET compared to control group, as well as association with objective measures, were also reported in the SLF that is partially involved in motor functions (Makris et al., 2005). The SLF represents a complex fiber bundle that facilitates executive functioning but also encodes the position of the body in the surrounding space and monitors complex motor activities (Makris et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White matter alteration in ET compared to control group, as well as association with objective measures, were also reported in the SLF that is partially involved in motor functions (Makris et al., 2005). The SLF represents a complex fiber bundle that facilitates executive functioning but also encodes the position of the body in the surrounding space and monitors complex motor activities (Makris et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The SLF represents a complex fiber bundle that facilitates executive functioning but also encodes the position of the body in the surrounding space and monitors complex motor activities (Makris et al., 2005). Thus, our data provide compelling evidence of an involvement of primary and associative motor tracts in ET.…”
Section: Discussionmentioning
confidence: 99%
“…In the regression analyses conducted separately on data from the young and older age groups, the only ROI that showed an RT-FA association in both groups was the left SLF. Results from DTI-based tractography studies suggest that this portion of the SLF originates at or near the supramarginal gyrus (BA 40), occupies the white matter of the pericentral and frontal opercular regions and connects with lateral prefrontal regions including pLIPC (BA 44/6), and DLPFC (BA 46) (Makris et al, 2005;Catani et al, 2005). The notion that switch cost RT is influenced by microstructural properties of WM linking left lateral prefrontal and parietal cortical regions is intriguing because it is in-keeping with previous functional neuroimaging results suggesting that executive control tasks require the coordinated activity of lateral prefrontal and parietal cortical regions (Cabeza and Nyberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…So far, heritability of regional white matter densities in pediatric twins was unknown. The fronto-occipital fascicle (FOF) and superior longitudinal fascicle (SLF) have been suggested to be involved in visuospatial processing (FOF) and language processing (SLF) [Makris et al, 2005;. Interestingly, in an earlier study in adult twin pairs, the FOF and parts of the corpus callosum were also found to be highly heritable [Hulshoff Pol et al, 2006].…”
Section: Discussionmentioning
confidence: 99%